Study of correlations between dental pathology and headache in adult patients (literature review) - Drogomyretska, Мирослава Стефанівна; Yezerska, Орися Орестівна (Actual Dentistry, 2024)
Introduction. Headache is the sixth leading cause of disability worldwide and the third leading cause of disability among people aged 50 years and older. Primary headaches are accompanied by a complex of musculoskeletal orofacial pain known as temporomandibular disorders (TMD). At the same time, the Diagnostic Criteria for TMD (DC/TMD) defined the category of secondary “headache associated with TMD” (HATMD). Purpose: based on the analysis of literary sources, to determine correlations between pathological conditions of the dental and jaw system and headache in adult patients. Materials and methods. Information search and analysis of scientific sources was carried out using scientometric databases Web of Science, PubMed, Google Scholar over the past 15 years. Conclusion. The results of numerous scientific studies presented in the review confirm the existence of correlations between pathological conditions of the maxillofacial system and headache in adult patients and the need for a multidisciplinary approach to their complex treatment. Keywords: headache, orofacial pain, temporomandibular disorders, periodontal tissue pathology, bruxism.